2013
DOI: 10.1167/iovs.13-11911
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Five-Year Incidence of Blindness and Visual Impairment in Urban Southern China: The Liwan Eye Study

Abstract: The incidence of VI in urban Southern China is high. The major causes are unoperated cataract and undercorrected refractive error, reflecting the need for better surgical and refractive care, even in this urban setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
3
30
2
Order By: Relevance
“…When compared with studies conducted in China, the Beijing Eye Study only reported incidence of best‐corrected VI (1.7%) . The Liwan Eye Study, which is also based on an urban Southern Chinese population, reported a higher incidence of PVI compared with our study (WHO criteria, 12.4% vs 8.33%; US criteria, 20.6% vs 12.2%) . This could largely be attributed to that participants in the Liwan Eye study were relatively older (mean age: 63.4 years old), as the age‐specific VI incidence using the US criteria for participants aged 50‐59 and 60‐69 in our study (8.5% and 20.1%, respectively) were higher than the corresponding figures in Liwan (2.5% and 6.0%, respectively).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…When compared with studies conducted in China, the Beijing Eye Study only reported incidence of best‐corrected VI (1.7%) . The Liwan Eye Study, which is also based on an urban Southern Chinese population, reported a higher incidence of PVI compared with our study (WHO criteria, 12.4% vs 8.33%; US criteria, 20.6% vs 12.2%) . This could largely be attributed to that participants in the Liwan Eye study were relatively older (mean age: 63.4 years old), as the age‐specific VI incidence using the US criteria for participants aged 50‐59 and 60‐69 in our study (8.5% and 20.1%, respectively) were higher than the corresponding figures in Liwan (2.5% and 6.0%, respectively).…”
Section: Discussioncontrasting
confidence: 69%
“…Given refractive error is the main cause of VI globally, appropriate spectacle correction is the most effective way to address this burden . Previous studies investigating the spectacle coverage rate (SCR) in China reported varying rates ranging from 44.1% to 71.2% .…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence rate (persons per 1000 per year) for the majority of studies (eight) was between 0.2 and 0.9 (US classifications) and 0.1 and 0.5 (WHO classifications). 8–10,23,2528 Only two studies were higher, at 1.1 (US) and 2.1 (WHO) for the Barbados Eye Study 24 and 1.2 (US) and 2.4 (WHO) for the Nakuru Eye Disease Cohort Study, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6] Unlike many ocular diseases, refractive error can be easily corrected if there are no myopiarelated complications which affect the macula permanently, such as lacquer cracks, choroidal neovascularization or retinal detachment. Such complications tend to affect individuals with pathological myopia due to an excessively elongated globe.…”
Section: Introductionmentioning
confidence: 99%